Roles of wind stress and thermodynamic forcing in recent trends in Antarctic sea ice and Southern Ocean SST: an ocean-sea ice model study - Kusahara, K; Guy Williams; Robert Massom; Phillip Reid; Hasumi, H (2017)
In contrast to a strong decrease in Arctic sea ice extent, overall Antarctic sea ice extent has modestly increased since 1979. Several hypotheses have been proposed for the net Antarctic sea ice expansion, including atmosphere/ocean circulation and temperature changes, sea ice-atmospheric-ocean feedback, increased precipitation, and enhanced basal meltwater from ice shelves. Concomitant with this positive trend in Antarctic sea ice, sea surface temperatures (SSTs) over the Southern Ocean south of approximately 45°S have cooled over this period. However, the mechanisms responsible for the Antarctic sea ice expansion and the SST cooling trend remain poorly defined. Here, we conduct comprehensive sensitivity experiments using a coupled ocean-sea ice model with a steady-state ice shelf component in order to investigate the main drivers of recent trends in Antarctic sea ice and SST over the Southern Ocean. The results suggest that Antarctic sea ice expansion is mostly explained by trends in the thermodynamic surface forcing, notably cooling and drying and a reduction in longwave radiation. Similarly, thermodynamic forcing is found to be the main driver of the zonal SST cooling trend. While apparently less influential on sea ice extent and SST, wind stress plays a key role in sea ice motion, thickening coastal sea ice, and thinning and decreasing the concentration of ice in mid-pack regions of the Amundsen-eastern Ross seas and 65–95°E in winter-spring. Furthermore, the model suggests that ocean-ice shelf interaction does not significantly influence the observed trends in Antarctic sea ice coverage and Southern Ocean SST in recent decades.